Structural and Petrologic Relations across the Grenville Province-Southern Province Boundary, Sudbury District, Ontario - Henderson, John R. (My University, 1967)
A region across the Grenville province-Southern province boundary was mapped, described and analysed. Structural fabric analyses and relationships between deformation and metamorphism were emphasized; especially in regard to Southern province rocks that were strained and recrystallized during the final Grenville orogenic episode.
Critical review of the literature on the region showed that metasedimentary rocks in the research area belong to the Huronian System, and that a granitic body of batholithic size was emplaced more than 600 million years before it was recrystallized last.
Many tectonite fabrics were shown to be products of homogeneous strain, and, wherever possible, principal strain axes were determined in relation to fabric symmetry axes. Comparison of internal fabrics of salt domes with structural fabrics in the research area indicated that the principal flowage occured in the direction of maximum elongation. Finally, the Grenville-Southern province boundary was defined genetically as a dynamo-thermal metamorphic gradient.
Title: Structural and Petrologic Relations across the Grenville Province-Southern Province Boundary, Sudbury District, Ontario, Author: John R. Henderson, Location: Thode